(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The main goal of the researchers was to come up with a business that will provide a unique variety of burrito not only in Novaliches, Quezon City but also in its neighboring cities. Juan Burritos’ business proponents randomly conducted a survey of fifty respondents. The survey took place in the business’ proposed location. The proponents also conducted a food tasting with the respondents. The data gathered and collected were used as a reference for enhancing the production of the product of the proposed business. Based on the survey, the proposed product has great opportunity to succeed in the market. The innovation of flavors of burritos seemed to be a big hit to the target consumers. The business proponents created a formal survey that determined the demographic profiles of the target market and sets of questions with corresponding indicators. The result of the survey was used by the researchers for data analysis. Based on the survey conducted, most of the respondents liked most the new taste of Burrito’s in affordable price. The idea of using a folding fan and social media as an alternative marketing strategy can be very helpful in starting a business. The researchers want to expand the channels of promotion and add a new product line or service for the growth of business.